2005
DOI: 10.1037/0022-006x.73.4.634
|View full text |Cite
|
Sign up to set email alerts
|

Couple-Focused Group Intervention for Women With Early Stage Breast Cancer.

Abstract: This study examined the efficacy of a couple-focused group intervention on psychological adaptation of women with early stage breast cancer and evaluated whether perceived partner unsupportive behavior or patient functional impairment moderated intervention effects. Two hundred thirty-eight women were randomly assigned to receive either 6 sessions of a couple-focused group intervention or usual care. Intent-to-treat growth curve analyses indicated that participants assigned to the couples' group reported lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
127
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 33 publications
9
127
1
2
Order By: Relevance
“…This response rate reflects (a) the burden of the intensive design of the study as patients were asked to complete a broad range of questionnaires, and (b) perhaps more importantly, the consent procedure required by the Institutional Review Board and the initiative it required from the patients to enroll in the study. Nonetheless, this percentage is comparable to what has been found in some well-resourced studies investigating couples [33,34]. The main reason (31%) for not participating was that couples indicated that participating was too great a burden.…”
Section: Data Collectionsupporting
confidence: 64%
“…This response rate reflects (a) the burden of the intensive design of the study as patients were asked to complete a broad range of questionnaires, and (b) perhaps more importantly, the consent procedure required by the Institutional Review Board and the initiative it required from the patients to enroll in the study. Nonetheless, this percentage is comparable to what has been found in some well-resourced studies investigating couples [33,34]. The main reason (31%) for not participating was that couples indicated that participating was too great a burden.…”
Section: Data Collectionsupporting
confidence: 64%
“…Interventions were grouped into two categories according to their main therapeutic approach: 'Cognitive Behavioural Skills Training' (CBST) (n=25), which focuses on illness cognitions, education, goal setting, and coping strategies such as problem solving and symptom management; and 'Relationship Counselling' (RC) (n=10), which addresses relationship difficulties such as sexual intimacy, partner supportiveness, and communication [38,51,45,52,53,54,55,56,57,58]. There was no noticeable effect of mode of delivery (faceto-face, telephone, online) on illness type or outcomes.…”
Section: Intervention Outcomesmentioning
confidence: 99%
“…When compared with a patient-only or control group, interventions which contained a module which provided techniques for managing and/ or sharing difficult emotions, effectively reduced depression and emotional distress among couples [67,36,43,60,51,64,61,52,39,56,58], and anxiety [45] and perceived stress [44] in partners.…”
Section: Emotional Outcomes (Across All Interventions)mentioning
confidence: 99%
“…Some psychological programs have been developed for couples coping with breast cancer (e.g., Baucom et al, 2009;Manne et al, 2005;Scott, Halford, & Ward, 2004). There is, however, little information about the effectiveness of psychological interventions for couples coping with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that women with breast cancer identify their partners as their main source of support and that this support plays an important role in women's psychological well-being and adjustment to the disease as well as in their physical health (e.g., immune function) (Baider, Ever-Hadani, Goldzweig, Wygoda, & Peretz, 2003;Baucom et al, 2012;Manne et al, 2005;Stiell, Naaman, & Lee, 2007;Weihs, Enright, & Simmens, 2008). However, partners are not always able to respond in a helpful and supportive way because of their own psychological distress, problems in the couple relationship, or complicated motivations about caregiving (e.g., acting to avoid feeling guilt, following social expectations about a proper role, or to find a sense of purpose and fulfillment in caregiving task).…”
Section: Introductionmentioning
confidence: 99%